Teachers' perception on the vitality of the English language among primary school students - How, Soo Ying; Abdullah, Ain Nadzimah; Tan, Helen (Universiti Putra Malaysia Press, 2018)
In this multilingual milieu, Malaysians in their early age are given choices to use particular language in the various domains of usage. As such, it is rather common to have Malaysians speaking at least two if not more languages. Bringing the attention to English language, despite its status as the second most important language in the nation and is commonly known as the second language, English is gradually slanted towards a foreign language more than a second language (Platt & Weber, 1980; Nunan, 2003). Thus, it is of interest to examine the vitality of languages at the primary level of education as indicative of an early stage of language vitality. Although studies of language vitality are often linked to minority and indigenous languages, language vitality in the present study has broadened to encompass the main languages in the nation. Qualitative methodological approach was employed. Interviews were conducted with primary school teachers to obtain insights on the vitality issues. The study identified possible higher vitality of English language when students become older. It is seen that there are many folds of the vitality of English language and that it cannot be measured by scale alone. It is found that social milieu (in the sense of urban area versus rural area), socio-economic background and language policies contribute to the differences in the experience of the English language among students and thus influencing the vitality of the language.